Pengaruh Kualitas Pelayanan dan Harga Terhadap Niat Berkunjung Ulang dengan Kepuasan Pelanggan Sebagai Variabel Intervening pada kebun Binatang Surabaya - Mochamad Aziz; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Service quality is one of the things that triggers repeat visit intentions to tourist attractions. This study investigates the effect of service quality and price on customer satisfaction. It also investigates whether customer satisfaction is a good mediator. This study conducted a survey on tourists at the Surabaya Zoo. Using purposive sampling method with sample criteria are tourists who have visited at least 2 times, 94 respondents were obtained. The data was then analyzed using Structural Equation Modeling. The findings show that service quality and price contribute positively to customer satisfaction. The study also proved that customer satisfaction mediates the relationship between service quality and price on tourists' repeat visit intention. This study contributes to understanding consumer behavior using the framework of customer satisfaction and revisit intention in tourism service objects, which can also be applied to other general companies.